2006
DOI: 10.1111/j.1525-1438.2006.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression-free interval in ovarian cancer and predictive value of an ex vivo chemoresponse assay

Abstract: The study objective was to determine the effectiveness of a phenotypic chemoresponse assay in predicting response to chemotherapy measured by progression-free interval (PFI) in a retrospective series of ovarian cancer patients whose tumor specimens had been tested with the ChemoFx assay. A statistically significant correlation between assay prediction of response and PFI was observed in 256 cases with an exact or partial match between drug(s) assayed and received. In 135 cases with an exact match, the hazard r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…Другие исследователи не смогли выявить пре-имуществ методов индивидуальной оценки хими-очувствительности перед протокольными и заняли отрицательную позицию [22,27,28]. Третьи авторы, установив лишь частичные преимущества в персо-нифицированном тестировании химиочувствитель-ности, заняли промежуточную позицию [22,27]. Нередко наблюдения по сопоставлению результатов in vitro и ex vivo были малочисленны, а если и име-ли представительную выборку, то не были аккуратно спланированы.…”
Section: результаты и обсуждениеunclassified
“…Другие исследователи не смогли выявить пре-имуществ методов индивидуальной оценки хими-очувствительности перед протокольными и заняли отрицательную позицию [22,27,28]. Третьи авторы, установив лишь частичные преимущества в персо-нифицированном тестировании химиочувствитель-ности, заняли промежуточную позицию [22,27]. Нередко наблюдения по сопоставлению результатов in vitro и ex vivo были малочисленны, а если и име-ли представительную выборку, то не были аккуратно спланированы.…”
Section: результаты и обсуждениеunclassified
“…In a 2006 study, progression free intervals were nearly three times longer in ovarian cancer patients who received a drug(s) to which they had tested responsive by ChemoFx than in patients who received a drug(s) to which they had tested non-responsive by ChemoFx. 45 A 2010 study found that the median overall survival in patients with primary ovarian cancer was at least 33% higher for those receiving a drug to which their tumors were classified as responsive by ChemoFx than for those receiving a drug to which their tumors were classified as non-responsive by ChemoFx. 46 Finally, breast cancer patients whose tumors tested responsive to docetaxel/capecitabine (TX) by ChemoFx were three times more likely to reach pathological complete response (pCR) when treated with TX than those whose tumors tested non-responsive by ChemoFx.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…16 Results from ChemoFx can help to predict patient responses to chemotherapy for treatment of ovarian cancer and may be helpful to identify drugs to which tumors are non-responsive (NR). 17,18 Recently, we reported that testing for sensitivity to erlotinib, an EGFR tyrosine kinase inhibitor, in the ChemoFx DRM was feasible. In addition, the results from testing tumors from patients with NSCLC with erlotinib using the ChemoFx DRM were similar to published response rates for patients treated with erlotinib clinically, indicating that the ChemoFx DRM may be helpful to identify patients whose tumors may be responsive to erlotinib.…”
Section: Introductionmentioning
confidence: 99%